Correction to: Estimation of bulk permittivity of the Moon’s surface using Lunar Radar Sounder on-board Selenological and Engineering Explorer - Keigo Hongo; Hiroaki Toh; Atsushi Kumamoto (Earth, Planets and Space, 2021)
An amendment to this paper has been published and can be accessed via the original article.